STRATEGI SOSIALISASI LITERASI MEDIA AKUN INSTAGRAM @japelidi - Saptiyono, Ami (Master of Communication Science Program, Universitas Diponegoro, 2024)
Technological developments are changing the landscape of information production, resulting in a flood of information. Not all of the information produced is true, much of it is false and misleading. This has moved the Media Literacy Support Network (Japelidi) to move to improve media literacy and has held many literacy activities and promotions, to invite the public to be aware of literacy. Through a qualitative research method using James Dilliard's Goals-Plans-Action Model theory, researchers observed the @japelidi Instagram account as the object of research and strengthened the data by conducting interviews with related parties, such as administrators and followers. The results of this study show that the unit of analysis does not appear in the content planning strategy with the dimensions of dominance and control. The dimension of power differences felt by both parties in persuasive interactions is not visible, marked by the empty comment column on each upload, and automatically also shows the absence of the control dimension, because there is no illustration of the communicator's ability to persuade or force others to comply. In its strategic actions, Japelidi has not shown the existence of mature strategic level plans, when viewed from the date of upload, intensity and quantity of uploads. This means that at the strategic action planning level, Japelidi does not yet have scheduling and consistency of content uploads aimed at educating digital media literacy.